Al-Akhtā’ al-Naḥwiyyah fī al-Rasā’il al-Jami’iyyah li Marḥalah al-Bakālūrīs fī al-Jāmi’ah - Masyruhin, Ahmad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to analyze Arabic Syntax errors in undergraduate-level written work at IAIN Ponorogo. This research is qualitative because of the type of data collected in words and behavior and the data obtained by the document Analysis. Researchers use the data analysis model Miles and Huberman. The results of the study are: 1) The error on the Isim read by Rafa 'consists of fail, Na'ibul Fa'il, Mubtada,' Khobar, Isim Kana, and Tawabi 'Lil Marfu' consisting of Na ' at and Taukid. 2) error on the Isim-item in the read Nasab consists of Maful Bih, Khobar Kana, Isim Inna, and Maf'ul Mutlaq. 3) errors in the texts that are read Jer consists of Jar Majrur, Idlofah, and Tawabi 'Lil Majrur that Na'at.